Recent progress of electromagnetic wave absorbers: A systematic review and bibliometric approach - Akinay, Yuksel; Gunes, Umit; Colak, Bektas; Cetin, Tayfun (KEAI PUBLISHING LTD, 2023)
The electromagnetic wave absorption capabilities of an absorber depend on its dielectric and magnetic components, which determine its interfacial polarization, conductivity loss, magnetic loss, and other such mechanisms. In this study, a comprehensive review of the electromagnetic wave and material interaction was conducted. Moreover, for a better understanding of the trends and evolutionary developments in the study of the electromagnetic wave absorber, 23300 documents dated between 1990 and 2020 were examined, which were obtained from Scopus using the keywords of electromagnetic wave absorption and microwave absorption . The data search in Scopus was conducted using the related keywords in the search bar for titles and abstracts. These results demonstrate that the majority of research regarding electromagnetic wave absorbers was conducted in China, which was followed by the United States. The number of published documents regarding the electromagnetic wave absorption field significantly increased between 1990 and 2020; these documents were mostly published as journal articles. With respect to the journal activity, the most productive journal was the Journal of Alloys and Compounds , with a total of 592 articles. In addition, graphene and titanium dioxide were determined to be the materials that were most studied in the field of electromagnetic wave absorption.
Keywords: Electromagnetic wave absorption; Microwave absorption; Bibliometric approach; Reflection loss; Composites; MICROWAVE-ABSORPTION; CARBON NANOTUBES; COMPOSITE; LIGHTWEIGHT; GRAPHENE; NANOCOMPOSITES; FABRICATION; FERRITE; Chemistry; Materials Science